Therapeutic effects of nerve growth factor‐targeting therapy on bladder overactivity in rats with prostatic inflammation. Issue 16 (1st October 2021) - Igarashi, Taro; Tyagi, Pradeep; Mizoguchi, Shinsuke; Saito, Tetsuichi; Furuta, Akira; Suzuki, Yasuyuki; Egawa, Shin; Wang, Zhou; Yoshimura, Naoki
Abstract: Background: The present study examined the effect of liposomes conjugated with antisense oligonucleotide of nerve growth factor (NGF‐OND) on local overexpression of NGF and bladder overactivity using rats with prostatic inflammation (PI). Methods: Male Sprague‐Dawley rats were divided into three groups: (1) Control group; intact rats, (2) PI‐NS group; rats with PI and intravesical instillation of normal saline (NS), (3) PI‐OND group; rats with PI and intravesical instillation of NGF‐OND. On Day 0, PI was induced by intraprostatic 5%‐formalin injection. On Day 14, NGF‐OND or NS was instilled directly into the bladder after laparotomy. On Day 28, therapeutic effects of NGF‐OND were evaluated by awake cystometry and histological analysis as well as reverse‐transcription polymerase chain reaction measurements of messenger RNA (mRNA) levels of NGF in the bladder and prostate, inflammatory markers in the prostate, C‐fiber afferent markers, and an A‐type K + channel α‐subunit (Kv 1.4) in L6‐S1 dorsal root ganglia (DRG). Results: Intravesical NFG‐OND treatment reduced PI‐induced overexpression of NGF in both bladder and prostate, and reduced PI‐induced bladder overactivity evident as longer intercontraction intervals in association with reductions of TRPV1 and TRPA1 mRNA expression levels in DRG. mRNA expression of Kv1.4 in DRG was reduced after PI, but improved in the PI‐OND group. Conclusions: These results indicate that NGF locally expressed in the bladder is an important mediator inducing bladder overactivity with upregulation of C‐fiber afferent markers and downregulation of an A‐type K + channel subunit in DRG following PI, and that liposome‐based, local NGF‐targeting therapy could be effective for not only bladder overactivity and afferent sensitization, but also PI. Thus, local blockade of NGF in the bladder could be a therapeutic modality for male LUTS due to BPH with PI.